2014
DOI: 10.7727/wimj.2013.223
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Intraepithelial Neoplasia in a Cohort of HIV-positive Women at the University Hospital of the West Indies: Management and Outcome

Abstract: HIV increases the risk of recurrence of CIN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…There are LMIC‐adapted versions of thermal ablation device, which are portable, affordable and battery‐powered. Studies have evaluated thermal ablation in different LMICs including in Jamaica, 19 Malawi, 16 India, 20,21 Brazil, 22 Bangladesh, 23 Nigeria, 24 Cameroon, 25,26 Honduras 27 and Zambia 28 . However, a major limitation of these studies was suboptimal verification of disease at follow‐up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are LMIC‐adapted versions of thermal ablation device, which are portable, affordable and battery‐powered. Studies have evaluated thermal ablation in different LMICs including in Jamaica, 19 Malawi, 16 India, 20,21 Brazil, 22 Bangladesh, 23 Nigeria, 24 Cameroon, 25,26 Honduras 27 and Zambia 28 . However, a major limitation of these studies was suboptimal verification of disease at follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…Among 170 women treated by thermal ablation, only 2.3% required more than two applications of the probe to cover the TZ. For women with histologically confirmed CIN at baseline, the follow-up outcomes are described in 19 Malawi, 16 India, 20,21 Brazil, 22 Bangladesh, 23 Nigeria, 24 Cameroon, 25,26 Honduras 27 and Zambia. 28 However, a major limitation of these studies was sub- The WHO recommends that thermal ablation should be provided at a minimum of 100 C for 20 to 30 seconds using as many applications as needed to cover the entire TZ.…”
Section: Adverse Effects and Complicationsmentioning
confidence: 99%
“…Fruchter et al [ 38 ] found recurrence to occur in 62.0 % of HIV-positive women compared to 18.0 % of HIV-negative women 36 months after treatment by either ablation or excision. Bambury et al [ 39 ] reported a recurrence rate of 66.2 cases per 100 person-years in HIV-positive women compared to 3.0 per 100 person-years in HIV-negative women following treatment by thermo-coagulation or LLETZ. The main attraction of ablative or excisional treatment after VIA/VILI is the opportunity to reduce or eliminate repeated clinic visits.…”
Section: Discussionmentioning
confidence: 99%
“…This is essential among WLWH, given the higher prevalence of CIN 11,13 and the worse treatment outcomes among this population compared with HIV-negative women. 45-47 …”
Section: Discussionmentioning
confidence: 99%